Lipid nanoparticle and polyplex nanomicelle for mRNA delivery - Itaka, Keiji; Xuan, Du (Drug Delivery System, 2024)
Lipid nanoparticles（LNPs）, which are a typical DDS used in mRNA vaccines, and polyplex nanomicelles that can deliver mRNA without causing inflammation at the administration site, are evaluated using the same mRNA under the same conditions. LNP yielded high levels of protein expression with inflammation at the injection site. In contrast, nanomicelles provided less but sustained protein production, with almost no inflammation at the injection site. It is important to have a variety of DDS options, which would be suitable for various purposes and administration route, for future mRNA drug development.